PENGARUH TAX AVOIDANCE DAN STRUKTUR KEPEMILIKAN TERHADAP COST OF DEBT - Alfiyan Abdussaid (Jurnal Penelitian Akuntansi (JPA), 2021)
This research aims to determine the effect of tax avoidance and ownership structure which is divided into institutional, family, and managerial ownership on cost of debt of all non-financial companies listed in Indonesia Stock Exchange for the 2015 – 2019 period. The type of this research is quantitative research that uses secondary data based on annual report. Sample from this research consisted of 75 companies. The Random Effect Model (REM) with panel data regression was used in this study using STATA version 14. Techniques analyzing data in this research used regression model selection test, classical assumption test, multiple linier regression, and partial hypotesis testing (T test). Based on the result of data analysis, it can be concluded that (1) tax avoidance has a negative significant effect on cost of debt, (2) institutional ownership has no effect on cost of debt, (3) family ownership has no effect on cost of debt (4) managerial ownership has no effect on cost of debt  and control variable, namely (5) company size has no effect on cost of debt